2013
DOI: 10.1002/mrm.24948
|View full text |Cite
|
Sign up to set email alerts
|

Divalent metal transporter, DMT1: A novel MRI reporter protein

Abstract: Manganese (Mn)-enhanced MRI (MEMRI) has found a growing number of applications in anatomical and functional imaging in small animals, based on the cellular uptake of Mn ions in the brain, heart and other organs. Previous studies have relied on endogenous mechanisms of paramagnetic Mn ion uptake and enhancement. To genetically control MEMRI signals, we reverse engineered a major component of the molecular machinery involved in Mn uptake, the divalent metal transporter, DMT1. DMT1 provides positive cellular enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…Of interest, we previously showed that by engineering glioma cells to overexpress the Divalent Metal Transporter, DMT1, we were able to convert negative to positive contrast using the same MEMRI protocol. 53 This suggests that Mn uptake and storage is likely to be highly dependent on the set of F I G U R E 1 0 Results from the PLX5622 preclinical trial show response to therapy is heterogeneous and tumor model-dependent. (A) From the aggregate longitudinal tumor volume data from the aSmo-1 model, it was apparent that growth of CTL-treated tumors (blue) did not differ significantly from the growth of PLX-treated tumors (red) after treatment start at W7.…”
Section: F I G U R E 7 Tumor Centroid and Heatmap Analysis Illustratesmentioning
confidence: 99%
“…Of interest, we previously showed that by engineering glioma cells to overexpress the Divalent Metal Transporter, DMT1, we were able to convert negative to positive contrast using the same MEMRI protocol. 53 This suggests that Mn uptake and storage is likely to be highly dependent on the set of F I G U R E 1 0 Results from the PLX5622 preclinical trial show response to therapy is heterogeneous and tumor model-dependent. (A) From the aggregate longitudinal tumor volume data from the aSmo-1 model, it was apparent that growth of CTL-treated tumors (blue) did not differ significantly from the growth of PLX-treated tumors (red) after treatment start at W7.…”
Section: F I G U R E 7 Tumor Centroid and Heatmap Analysis Illustratesmentioning
confidence: 99%
“…To address the potentially restrictive role of iron import machinery, one study proposed co-expressing Ft with the transferrin receptor, a natural participant in cellular iron transport [78]. A conceptually related strategy involves using overexpression of paramagnetic metal ion transporters themselves to induce MRI contrast; contrast changes in rodents have been reported using the magnetotactic bacterial protein MagA [79] and the mammalian divalent cation transporter DMT1 [80], but it is not clear which specific metalloproteins might be involved in binding the metal ions once they have entered cells.…”
Section: Natural Metalloproteins In Mrimentioning
confidence: 99%
“…Previous efforts to develop such reporters have focused primarily on two classes of proteins. In one class, metalloproteins and metal ion transporters are overexpressed to enrich the paramagnetic content of cells, thereby enhancing nuclear relaxation rates and producing contrast in T1 or T2-weighted MRI 9,[12][13][14][15][16][17][18][19][27][28][29] . In the second strategy, proteins with large numbers of basic amino acids are used to generate contrast through chemical exchange saturation transfer (CEST) between protein-bound and aqueous protons 6,8,21,22,25,30 .…”
Section: Introductionmentioning
confidence: 99%